2013
DOI: 10.1038/srep01350
|View full text |Cite
|
Sign up to set email alerts
|

Collapsin response mediator protein 3 deacetylates histone H4 to mediate nuclear condensation and neuronal death

Abstract: CRMP proteins play critical regulatory roles during semaphorin-mediated neurite outgrowth, neuronal differentiation and death. Albeit having a high degree of structure and sequence resemblance to that of liver dihydropyrimidinase, purified rodent brain CRMPs do not hydrolyze dihydropyrimidinase substrates. Here we found that mouse CRMP3 has robust histone H4 deacetylase activity. During excitotoxicity-induced mouse neuronal death, calpain-cleaved, N-terminally truncated CRMP3 undergoes nuclear translocation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…CRMP3 expression was also found to be altered in Down syndrome (Weitzdoerfer et al, 2001). Recent studies revealed that CRMP3 has histone H4 deacetylase (HDAC) activity (Hou et al, 2013). Dendrites are one of the most plastic structures of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…CRMP3 expression was also found to be altered in Down syndrome (Weitzdoerfer et al, 2001). Recent studies revealed that CRMP3 has histone H4 deacetylase (HDAC) activity (Hou et al, 2013). Dendrites are one of the most plastic structures of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…CRMP3, a novel histone H4 deacetylase is cleaved by over-activated calpain in neurons undergoing excitotoxic neuronal death (Hou et al, 2013;Hou et al, 2006). Under physiological conditions, full-length CRMP3 does not exhibit histone H4 deacetylase activity…”
Section: Collapsin Response Mediator Protein 3 (Crmp3)mentioning
confidence: 99%
“…and resides in the cytosol. Upon cleavage by calpains at a site near the N-terminus, the truncated CRMP3 translocates into the nucleus where it exhibits robust histone H4 deacetylase activity, induces nuclear condensation and neuronal death (Hou et al, 2013).…”
Section: Collapsin Response Mediator Protein 3 (Crmp3)mentioning
confidence: 99%
“…C57B/6 mice (20 -23 g) were obtained from Charles River and bred locally. Under temporary isofluorane anesthesia, MCAO was induced by the intraluminal insertion of a silicon-coated nylon filament (Re L910 PK5, Doccol Corporation) through the common carotid artery into the internal carotid artery and left in place for 60 min as we previously described (20)(21)(22)(23)(24)(25)(26). Cerebral blood flow (CBF) was monitored by laser Doppler flowmetry using a probe located in the ipsilateral parietal bone (1-2 mm posterior to bregma), and a >90% reduction in CSF was considered to indicate successful occlusion.…”
Section: Methodsmentioning
confidence: 99%
“…The analytes were ionized by negative-ion electrospray using the following conditions: capillary potential 1.75 kV; desolvation gas flow 1100 L/h; cone gas flow 150L/h; and source and desolvation gas temperatures at 120 Cortical neuronal cultures-Primary cortical neurons were prepared from embryonic E15-16 CD1 mice and cultured in neurobasal media supplemented with B-27 and N2 (Invitrogen Canada) for 7 -14 days as previously described (20,24,25). Neurons in these cultures are fully mature and are responsive to glutamate induced excitotoxicity.…”
Section: Quantification Of Pa and Aba Metabolites By Uplc/ms/ms-analysismentioning
confidence: 99%